2015
DOI: 10.1590/s1679-45082015ao3242
|View full text |Cite
|
Sign up to set email alerts
|

Long-lasting endothelium-dependent relaxation of isolated arteries caused by an extract from the bark of Combretum leprosum

Abstract: Objective To describe and to characterize the relaxing effect of an extract of the bark of Combretum leprosum on isolated arterial rings from different animals.Methods Rings (3 to 4mm) from rabbit, rat, or porcine arteries rings were suspended in an organ bath (Krebs, 37°C, 95%O2/5%CO2) to record isometric contractions. After the stabilization period (2 to 3 hours) contractions were induced by the addition of phenylephrine (0.1 to 0.3µM) or U46619 (10 to 100nM), and Combretum leprosum extract was added on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…( Combretaceae ) is a shrub that grows in northeastern Brazil and the extracts from different parts are used to treat many illnesses. Alves Filho et al, [54] assayed the ethanolic extract of the bark of C. leprosum in IRA. The extract (1.5 µg/mL) induced EDR that was significantly reduced in the absence of extracellular Ca 2+ , and the relaxation was reverted by ruthenium red (a transient receptor potential channels blocker).…”
Section: Phytochemical Assays Of Plant Extracts and Isolated Compomentioning
confidence: 99%
See 1 more Smart Citation
“…( Combretaceae ) is a shrub that grows in northeastern Brazil and the extracts from different parts are used to treat many illnesses. Alves Filho et al, [54] assayed the ethanolic extract of the bark of C. leprosum in IRA. The extract (1.5 µg/mL) induced EDR that was significantly reduced in the absence of extracellular Ca 2+ , and the relaxation was reverted by ruthenium red (a transient receptor potential channels blocker).…”
Section: Phytochemical Assays Of Plant Extracts and Isolated Compomentioning
confidence: 99%
“…The extract (1.5 µg/mL) induced EDR that was significantly reduced in the absence of extracellular Ca 2+ , and the relaxation was reverted by ruthenium red (a transient receptor potential channels blocker). Thus, it is suggested that the C. leprosum extract contains bioactive compounds that induce Ca 2+ -dependent stimulation of ECs, allowing a prolonged production of relaxing factors [54].…”
Section: Phytochemical Assays Of Plant Extracts and Isolated Compomentioning
confidence: 99%